An analysis of skin appendageal tumors: 10 year study - Dr. Junu Rajan; Dr. Apuca Susan Mathew; Dr. B Jayalekhmi (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Skin appendageal tumors are wide spectrum of disorders that differentiate towards one or more adnexal structures. Objective: To determine the prevalence of skin appengeal tumours. Materials and methods: This is a record based cross sectional study from the Department of pathology, Dr SMCSI Medical College between 1st January 2004 to 1st November 2014 who were diagnosed with skin tumours by histopathology and these cases were reviewed classified and analysed according to the patient’s age, gender, and localization. Results: 166 cases were studied during this study period, males 68 and females 98. Mean age of presentation in this study was 34 years. Tumours with follicular differentiation constituted the maximum, 81 cases (48.8%), followed by eccrine differentiation constituting 22 cases (13.25%): tumours with apocrine differentiation 21cases (12.66%) and sebaceous differentiation 9 cases (5.4%). One case each of sebaceous adenoma and sebaceous carcinoma were the only malignant tumours. Conclusion: Skin adnexal tumours are relatively uncommon and the incidence of benign skin adnexal tumours are more common compared to the malignant ones.